Programmable bandwidth-variable optical temporal differentiator based on linearly chirped fiber bragg grating and digital thermal controller - Wang, Ruoxu (2018)
We experimentally demonstrate an all-fiber structured bandwidth variable second-order optical temporal differentiator based on linearly chirped fiber Bragg grating and digital thermal controller. The bandwidth can be reconfigured from 0.55 nm to 0.8 nm.